A Comparative Analysis of House Owners in Need of Energy Efficiency Measures but with Different Intentions - Robert Baumhof; Thomas Decker; Klaus Menrad (Energies, 2019)
Existing private homes in Germany and throughout Europe often are in need of energy efficient refurbishment measures (EERMs). However, these EERMs are not realized on the required level in order to achieve environment-related political targets. Therefore we investigate, based on an online survey of 1085 German owner-occupiers, the factors that differentiate two groups of single- and two-family house owners in need of EERM. Using an extended version of the Theory of Planned Behavior as a research framework, the performed logistic regression analysis shows that e.g., behavioral beliefs are significant factors for differentiating “Future-Refurbishers” from “Non-Refurbishers”. Based on our results we suggest an enhancement of practice-orientated initiatives, e.g., refurbishment workshops or best-practice presentations. By presenting the aesthetic appearance of refurbished buildings or providing knowledge, other owner-occupiers could be motivated to engage in EERM. In addition to funding programs, initiatives like this can be used to increase the general energy efficiency of buildings and specifically of those in cities and urban districts, where a high share of the mentioned houses is located and greenhouse gas emissions are caused to a great extent.